Fichte’s Conception of Law and Its Foundations - Saraya, Mahmoud (AUC Knowledge Fountain, 2025)
The question concerning the true nature of law has frequently arisen throughout the history of philosophy, and many different answers have been given to it. This thesis examines Johann Gottlieb Fichte’s Foundations of Natural Right (1796–1797), which exemplifies an approach to understanding the nature of law by inquiring into its metaphysical foundations. Fichte provides a conception of law founded upon the possibility of the existence of an external world, individuality, and intersubjectivity. Law, as a moment of human self-consciousness, becomes a necessity, a condition of self-consciousness, and the ultimate foundation of human existence. Fichte’s theory shows the preconditions for establishing a liberal political order, which is the aim of the book and is inextricably connected with realizing the true nature of human beings as free and rational individuals. The Foundations is considered to be Fichte’s most comprehensive and sophisticated work in political philosophy where he analyzes law as a metaphysical and epistemological problem. This thesis explores Fichte’s question, “But what is the law?” and how this bare concept is to be realized in the sensible world? The thesis also examines the different interpretations of Fichte’s philosophy, questioning whether there is a reciprocal relation between morality and law, and whether he defends a legal system purified of moral theory or a politics shaped by morality. It provides an authentic explanation of the origin of many of the legal concepts used today, identifying the foundation of these concepts, and highlighting Fichte’s work as a model of the transformation of legal thinking in the modern world.